Financial sustainability of the banks: an experts’ assessment - Kuanova, L.A.; Akimbayeva, K.T.; Doszhan, R.D.; Gamidullaeva, L.A. (Journal of Economic Research & Business Administration, 2024)
The rise of sustainable finance, which involves financial tools operating within the framework of environmental, social, and governance principles adopted by companies and financial institutions, is gaining traction in major global markets. According to the Global Alliance for Sustainable Investments, these approaches already account for 35.9% of total invested assets. This trend is driven by a new global reality where long-term development cannot take place without addressing deepening environmental and social contradictions. The article aims to assess the priority of ESG of the banks as sustainable finance factors for the development of the recommendations, as the assessment of the ESG principles in the banks of the country allows for the identification of further courses of sustainable finance development. Furthermore, the investigation of leading countries’ experiences in environmentally and socially responsible investment and its role in the banking system reveals both common and specific features that could be effectively implemented in Kazakhstan. The research methodology entails experts’ assessment from the middle management level of the banks of ESG impact of 9 factors by AHP method. The AHP method allows investors to systematically compare and prioritize used ESG factors, that relates to their significance as the indicators for assessment the state and prospects for the ESG principles implementation in the bank’s activity in Kazakhstan. The obtained results allow to suggest that priority instruments for ESG promotion in the country are a legislative framework and the state program. The study illustrates that the integration of ESG factors into the strategy of sustainable development of banks contributes to the growth of their assets by increasing demand for sustainable products and attracting new customers. The findings have practical implications for banks related to sustainable finance and ESG criteria-based investing. Key words. Sustainable finance, ESG, decarbonization, banks, experts’ assessment.